The house that cheese built : the unusual life of the Mexican immigrant who defined a multibillion-dollar global industry - Leal, Miguel A. (Ascent Audio, 2023)
A quintessential American dream story from a Mexican entrepreneur who shares the tale of building a multi-million-dollar business from scratch, complete with both success and failure, and always a vision of hope. Leal came to the US penniless as a teenager, speaking almost no English; he literally slept in the boiler room of a Wisconsin cheese factory for months before he was caught. Through hard work, grit, and ingenuity Leal would go on to launch his own business. He is widely credited with introducing Mexican cheeses to the US market and grew his company to a multi-million-dollar success story that defined an industry. Yet, like many successful entrepreneurs, Leal's great successes were matched by personal failures: the end of a marriage; trouble with law enforcement; and the deeply felt sense that there must be something more to life than great wealth. Leal's memoir, The House that Cheese Built, is both a quintessential immigrant success story-one that beautifully illustrates the immigrant experiences: isolation, fear, and ambition for a better life and assimilation-as well as a thoughtful personal account of entrepreneurship and all its benefits and costs.